Tissue specificity in fasting glucose utilization in slightly obese diabetic patients submitted to bariatric surgery1. (16th April 2013) - Morbelli, Silvia; Marini, Cecilia; Adami, Gian Franco; Kudomi, Nobuyuki; Camerini, Giovanni; Iozzo, Patricia; Massollo, Michela; Capitanio, Selene; Bodrato, Samanta; Verardi, Maria Teresa; Papadia, Francesco; Cordera, Renzo; et al.
Abstract Objective: The present study was planned to investigate, by means of quantitative FDG‐PET, how bariatric surgery (BS) modifies the metabolic pattern of the whole body and different tissues in slightly obese patients with type 2 diabetes mellitus (T2DM). Design and Methods: Before, 1 and 4 months after BS, 21 consecutive slightly obese T2DM patients underwent blood sampling to estimate plasma levels of glucose, insulin, glycosylated hemoglobin. At the same time points, these patients underwent a dynamic 18F‐FDG PET study of thorax and upper abdomen in fasting state and after washout of T2DM therapy. Gjedde‐Patlak analysis was applied to estimate glucose uptake in the whole body and in different tissues (myocardium, skeletal back muscle, adipose tissue, and liver). Results: Surgical intervention quickly lowered levels of both insulin and glucose documenting an amelioration of glucose tolerance. Similarly, skeletal muscle and myocardial glucose uptake significantly increased soon after surgery (P < 0.001 and P < 0.01 at 1 month versus baseline, respectively) and remained substantially stable thereafter. By contrast, glucose uptake slightly decreased from its baseline values in the liver (P < 0.01 at 4 months) while no response could be documented over time in the adipose tissue. Conclusions: These findings document that BS‐induced modification of glucose homeostasis in slightly obese T2DM patients is mostly due to an increase in muscle glucose consumption. The surgically modified metabolic pattern of these patients might be of interest as a new model to investigate mechanism underlying insulin resistance.